Changing patterns of global nitrogen deposition driven by socio-economic development - Jianxing Zhu; Yanlong Jia; Guirui Yu; Qiufeng Wang; Nianpeng He; Zhi Chen; Honglin He; Xianjin Zhu; Pan Li; Fusuo Zhang; Xuejun Liu; Keith Goulding; et al. (Nature Communications)
Abstract Advances in manufacturing and trade have reshaped global nitrogen deposition patterns, yet their dynamics and drivers remain unclear. Here, we compile a comprehensive global nitrogen deposition database spanning 1977–2021, aggregating 52,671 site-years of data from observation networks and published articles. This database show that global nitrogen deposition to land is 92.7 Tg N in 2020. Total nitrogen deposition increases initially, stabilizing after peaking in 2015. Developing countries at low and middle latitudes emerge as new hotspots. The gross domestic product per capita is found to be highly and non-linearly correlated with global nitrogen deposition dynamic evolution, and reduced nitrogen deposition peaks higher and earlier than oxidized nitrogen deposition. Our findings underscore the need for policies that align agricultural and industrial progress to facilitate the peak shift or reduction of nitrogen deposition in developing countries and to strengthen measures to address NH3 emission hotspots in developed countries.